Does geographical discrimination exist in online lending in China: An empirical study based on Chinese loan platform Renren - Tianlei Pi; Yaosen Liu; Jiahui Song (International Journal of Financial Studies, 2020)
Background: Online lending has developed rapidly in China in recent years, into a typical Internet financial model. China's online lending related issues have received widespread attention from scholars. Methods: This study used 396,634 order data-points (935,037 original order data-points) from the Renren Loan website since its inception in January 2017. We used ordinary least squares (OLS) regression to study the problem of geographical discrimination in online lending in China, and we conducted two robust tests. Results: Studies have shown that significant geographical discrimination exists in China's online lending market. From the perspective of the lender, different investment intentions exist for borrowers from various regions, thereby leading to variations in the success rates of loans. From the perspective of the borrower, the belief exists that borrowers from different regions will have varying interest rates because of the effect of geographical discrimination. Conclusion: We believe that geographical discrimination is due to the effects of the economic, financial, educational, and ethnic conditions of the borrower's location on willingness to invest and the success rate of borrowing. However, borrowers' self-discrimination is primarily related to economic and ethnic differences among provinces.
Keywords: D80; H70; J71; 330; borrowing rate; geographical discrimination; online lending; success rate of borrowing